2002
DOI: 10.1366/0003702021954953
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognitions of Band Shifting, Overlapping, and Broadening Using Global Phase Description Derived from Generalized Two-Dimensional Correlation Spectroscopy

Abstract: In this paper we propose a new method for pattern recognitions of band shifting, overlapping, and broadening using a global phase map derived from generalized two-dimensional correlation spectroscopy (global 2D phase map). To obtain the distinct patterns for band shifting, overlapping, and broadening, original spectra are subjected to scaling so that the spectra after the scaling do not cross one another. After such pretreatment the band shifting creates the tilting of a correlation plane, the band overlapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…A large number of model spectral maps were compiled by these authors for the identification of peak patterns. Pattern recognition on features of 2D global phase maps was also attempted by Morita and Ozaki [77] based on band shift, overlapping, and broadening of peaks.…”
Section: Simulation For Better Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of model spectral maps were compiled by these authors for the identification of peak patterns. Pattern recognition on features of 2D global phase maps was also attempted by Morita and Ozaki [77] based on band shift, overlapping, and broadening of peaks.…”
Section: Simulation For Better Interpretationmentioning
confidence: 99%
“…2D global phase angle maps were used to study a Langmuir-Brogett film of dodecyl TCNQ under varying temperature [91]. Pattern recognition method was proposed for analyzing features of 2D global phase map based on band shift, overlapping, and broadening of peaks [77]. Chin and Lin [92] employed generalized 2D correlation as a useful tool to study reaction kinetics involving parallel reaction paths, as clear asynchronous peaks develop for reactant and product pairs.…”
Section: Coherence and Phase Anglementioning
confidence: 99%
“…It is worth noting that, during the transition from dynamic 2D-IR to generalized 2D-IR, the major advantages of the former were adopted. Despite of the generally accepted spectral resolution enhancement, a number of studies [19][20][21][22][23][24][25][26], including our systematic studies in polymers [27][28][29][30][31], have been carried out to investigate the effect of variables, such as overlapping bands, bandwidth change, peak shift and data set on the final results in generalized 2D-IR. It has been found that the new features revealed in the 2D plots do not necessarily correspond to real infrared absorption bands.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been applied, for example, to elucidate the photopolymerization of acrylic and epoxy monomers and to the transetherification and selfcondensation reactions in a melamine/formaldehyde resin [8,9]. In addition to the ability of correlation spectroscopy to characterize such temporal spectral changes it can be used to resolve complicated regions of a spectrum, identify band patterns, and interpret synchronous versus asynchronous correlation spectra [10][11][12].…”
Section: Introductionmentioning
confidence: 99%